Bioethics as a new direction in the moral and ethical discourse of modern society - Makhmudova, Aziza Nugmanovna (Science and Education, 2024)
In today’s article, we live in a time in which time and space are moved towards upgrade, human space is getting into the ground of development and scientific innovations, and we are living in an era. it has been explained that since thousands of years, the human being has always strived for the highest, strived for it, and worked tirelessly to create comfort and prosperity for himself.